Modification of pLL/DNA complexes with a multivalent hydrophilic polymer permits folate‐mediated targeting in vitro and prolonged plasma circulation in vivo - Ward, C; Pechar, M; Oupicky, D; Ulbrich, K; Seymour, L (Wiley, 2002)
Background: Gene delivery vectors based on poly(L‐lysine) and DNA (pLL/DNA complexes) have limited use for targeted systemic application in vivo since they bind cells and proteins non‐specifically. In this study we have attempted to form folate‐targeted vectors with extended systemic circulation by surface modification of pLL/DNA complexes with hydrophilic polymers. Methods: pLL/DNA complexes were stabilised by surface modification with a multivalent reactive polymer based on alternating segments of poly(ethylene glycol) and tripeptides bearing reactive ester groups. Folate moieties were incorporated into the vectors either by direct attachment of folate to the polymer or via intermediate poly(ethylene glycol) spacers of 800 and 3400 Da. Results: Polymer‐coated complexes show similar morphology to uncoated complexes, their zeta potential is decreased towards zero, serum protein binding is inhibited and aqueous solubility is substantially increased. Intravenous (i.v.) administration to mice of coated complexes produced extended systemic circulation, with up to 2000‐fold more DNA measured in the bloodstream after 30 min compared with simple pLL/DNA complexes. In further contrast to simple pLL/DNA complexes, coated complexes do not bind blood cells in vivo. Folate receptor targeting is shown to mediate targeted association with HeLa cells in vitro, leading to increased transgene expression. We demonstrate for the first time that DNA uptake via the folate receptor is dependent on pEG spacer length, with the transgene expression relatively independent of the level of internalised DNA. Conclusions: We show increased systemic circulation, decreased blood cell and protein binding, and folate‐targeted transgene expression using pLL/DNA complexes surface‐modified with a novel multireactive hydrophilic polymer. This work provides the basis for the development of plasma‐circulating targeted vectors for in vivo applications.